2020
DOI: 10.1186/s12888-020-02737-3
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of early identification and treatment of sleep disorders in mental health care: protocol of a randomized control trial

Abstract: Background: Sleep disorders are a risk factor for developing a variety of mental disorders, have a negative impact on their remission rates and increase the risk of relapse. Early identification and treatment of sleep disorders is therefore of paramount importance. Unfortunately, in mental health care sleep disorders are often poorly recognized and specific treatment frequently occurs late or not at all. This protocol-paper presents a randomized controlled trial investigating the clinical relevance of early de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The cohort is primarily white (93%), matching South Island demographics [18]. Assessments were carried out at birth and ages 3,5,7,9,11,13,15,18,21,26,32,38 and most recently (completed April 2019) 45 years, when 94.1% (n = 938) of the 997 participants still alive took part. At each assessment, participants were brought to the research unit for interviews and examinations.…”
Section: Age-38 Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The cohort is primarily white (93%), matching South Island demographics [18]. Assessments were carried out at birth and ages 3,5,7,9,11,13,15,18,21,26,32,38 and most recently (completed April 2019) 45 years, when 94.1% (n = 938) of the 997 participants still alive took part. At each assessment, participants were brought to the research unit for interviews and examinations.…”
Section: Age-38 Samplementioning
confidence: 99%
“…Moreover, loneliness is associated with poorer clinical outcomes among groups of people who receive treatment for mental health problems [3]. Loneliness may also be of interest to clinicians as a valuable individual risk indicator for psychopathology, as it is analogous to sleep problems or difficulties with concentration, which are present in a number of disorders and are included in widely used screening checklists such as the Patient Health Questionnaire and the Center for Epidemiological Studies Depression Scale [4][5][6]. Though not all individuals who experience loneliness will have co-occurring mental health problems, there is potential scope to utilise a loneliness measure alongside other information as part of a screening tool [7].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we expect that the classifier developed in this study will facilitate the screening of children's sleep disorders in multiple situations. A previous study showed that early detection and treatment of sleep disorders aided the treatment of mental disorders (34); therefore, use of the classifier may help improve mental status. In the future, we will further improve the accuracy of the automatic classifier by incorporating machinelearning techniques.…”
Section: Use By Parents Via An Applicationmentioning
confidence: 99%
“…5 Representation of mental health disorders could be seen in patients with moans of sleeping difficulty. 9 Weak physical conditions caused insomnia in Covid-19 patients. Insomnia was more influenced by psychological conditions when the virus infected the patient.…”
Section: Introductionmentioning
confidence: 99%